Головні убори із Бердянського кургану - Клочко, Л.С. (Археологія і давня історія України, 2020)
У пограбованій центральній могилі Бердянського
кургану залишилася незруйнована ділянка, на якій
in situ зафіксовано велику кількість декоративних
елементів. Особливу цікавість викликають золоті
пластинки-прикраси предметів жіночого вбрання:
головних уборів, одягу тощо. Пластинки-аплікації
розрізняються за розмірами та рельєфними зображеннями на поверхні. Визначення семантики образів дозволяє зробити припущення про особливий характер ділянки і речей, які поклали до могили при звершенні поховання. The Berdyansk kurgan has been studied for a long
time, however some problems remain unsolved. One of
them is the reconstruction of costume components by
decorative elements, found in central burial (N 2). It was
raided, however one area remained intact. Below the
collapsed ceiling is the «item storage»: there were items
of which only jewelry remained — the large amount of
golden applique plates (2991 items total). The most peculiar
are the artifacts which were probably the adornments
for the headwear. In order to recreate their form,
the complex and comparative analyses of golden plates’
collections were performed. The probably adorned coneshaped
hats and the veil. The one collection of adornments
included appliques which were on the frontal part
of the headwear. Below were the triangular plates, the
main part was occupied by ornamented appliques: «portraits
» full face (female image) and profile (grotesque
male image), felidae predator. The adornments of the
cone-shaped hat are connected to the other headwear —
the veil. It was ornamented on its edges — on the left
and on the right — with rectangular plates which contained
so-called «brotherhood scene». The connection of
the said images on the headwears is the marker of sacramental
act — wedding rituals.
The artifacts, which probably were ornaments of
headwear, draw most attention. The complex and
comparative analysis of golden jewelry was used in
order to recreate their form. It is possible that they
were attached to different types of attires. One attire
consisted of cone-shaped hat and the veil. They are
decorated with anthropomorphous images and geometrical
ornaments (triangles). Another attire is also
the cone-shaped hat, which form is supported by horizontal
lines of plates with the images of predators and
triangles. Generally speaking, these are the symbols
of fertility cult. One of the tasks of the research is the
determination of attire’s semantics. The grave contains
the burial of a high-rank man, but the reconstructed
attires are female. Cone-shaped attires are linked to
wedding ceremonies in many peoples. The burial and
wedding rituals have similar semantics, since both are
about passing from one world to another. Sacred attires
could have been the markers of bride’s (or brides’)
presence in the male burial.
Apart from the headwears there were also the necklace
which resembles the net and the clothes adorned
with golden appliques. The «item storage» was surrounded
by the golden plates, presumably sewed on the
veil, which had the images of the gryphon and felidae
hunter — the ornament which divides two worlds —
one of life, and the other of death.